Comparative Analysis of the Efforts of Highly Qualified Elite Armwrestlers with Different Strength Abilities - Dmytro Bezkorovainyi; Oleg Kamayev; Stanislav Vlasko; Leonid Plotnytskyi; Yevhen Kravchuk; Denis Kulakov; Oksana Mashchenko; Andrii Kliuka (OVS LLC, 2023)
Study purpose. Determination of the peculiarities of the manifestation of strength in competitive exercises of highly qualified armwrestlers with different strength abilities. Materials and methods. The study involved the 4 best armwrestlers in the world weighing from 80 to 100 kg (m = 87.50 ± 2.47 kg) in 2017-2020. Four power test exercises have been identified that ensure the performance of a competitive action in armwrestling: flexion of the fingers, stretch with a hammer, hook and bending the hand. Strength indicators in all test exercises were measured with an FL1K 0.5N, 1000N electric strain gauge dynamometer, Kern & Sohn GmbH (China), fixed on the armwrestling table using an author's block device. Results. The results of the correlation analysis of the relationships between the studied indicators confirm the presence of a difference in the direction and strength of the relationships between the strength and time characteristics of the efforts of athletes with different strength and speed-strength abilities. Thus, out of 36 correlation indicators, the data of armwrestlers 1 and 2 have 11 modules with very high connection strength (r = 0.926-0.999), of which 7 modules are with time and 4 modules are with force characteristics of efforts. Athletes 3 and 4 also have 3 modules with very strong connections (r = 0.916-0.948) and 8 modules with strong connections (r = 0.739-0.886), of which 7 modules are with strength indicators and 4 modules are related to time characteristics. But the other correlation indicators have very weak (r < 0.29) and weak (r = 0.3-0.5) levels of relationships. Conclusions. Analysis of the time and force characteristics of the manifestation of force in the process of achieving boundary resistance allows us to clearly establish the genetically determined speed and strength abilities of the explosive, fast and slow force of armwrestlers.